PUBLICIST TEXTS AND THEIR FEATURES IN TRANSLATION - Usmonova Umida Baxtiyorovna; Narbayeva Muhlisa Shavkat qizi (Web of Journals Publishing, 2023)
Nonfiction texts often include speeches by journalists and writers and scholars for various forms of media such as newspapers, magazines, television, radio, websites, etc. This article describes the features of journalistic text in translation.
Keywords: newspaper, text, work, meaning, attitude, essence of the text, speech process, stylistics, speech, information.